Mindstorms not just a kid's toy. - Wallich, P. (IEEE spectrum)
Robotic roller-coasters, mobile intelligent cat toys, a robotic disk jockey, an autonomous self-propelled video camera and a tiny mobile image scanner that builds up pictures by crawling millimeter by millimeter across a page are just some of the gadgets being produced by an R&D organization that few know even exists. The inventors are not part of a big research university or at some forward-looking computer company, but a loosely knit group of engineers who build gizmos out of Lego bricks. Developed by the Billund-based Danish toy company, some bricks contain microcomputer-controlled sensors and motors, and all are components of a three-year-old product called Lego Mindstorms